2019
DOI: 10.29252/wjps.8.1.58
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Topical Vitamin A and E on Ischemic Random Skin Flap Survival

Abstract: BACKGROUND Ischemia of skin flaps is an important complication in reconstructive surgery. This study evaluated the efficacy of topical vitamins A and E on improving flap survival. METHODS Twenty-four white-albino male rats were randomly divided into two groups of treatment and control. Standard rectangular, distally based dorsal random pattern skin flap was elevated. Intra-peritoneal cephazoline was administered to prevent any unexpected infection. No pharmaceutical age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Similarly, enhanced activity of natural cellular defense mechanisms against free radicals through topical/oral administration of tocopherols (vitamin E) and retinoids (vitamin A) or injection of ascorbate (vitamin C) and glutathione have been shown to improve flap survival significantly in rats [ 49 ]. Interestingly, various studies have also demonstrated an association between hyperthyroidism and oxidant-mediated tissue damage [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, enhanced activity of natural cellular defense mechanisms against free radicals through topical/oral administration of tocopherols (vitamin E) and retinoids (vitamin A) or injection of ascorbate (vitamin C) and glutathione have been shown to improve flap survival significantly in rats [ 49 ]. Interestingly, various studies have also demonstrated an association between hyperthyroidism and oxidant-mediated tissue damage [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%